2017
DOI: 10.23938/assn.0047
|View full text |Cite
|
Sign up to set email alerts
|

Calls due to suicidal behaviour made to the prehospital, emergency department in Málaga: characteristics and associated factors

Abstract: Material y métodos. Esta investigación consiste en un estudio observacional retrospectivo de las demandas registradas en la base de datos de la Empresa Pública de Emergencias Sanitarias durante un año. Las comparaciones y análisis de regresión logística multivariante se realizaron respecto a la edad y sexo de los demandantes y respecto a las siguientes características de las demandas: horas del día, días laborables o festivos, meses del año y trimestres, número de recursos movilizados y tipos de resolución.res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
3
2
1
Order By: Relevance
“…The average age of our sample (43.2 years) is similar to previous studies (1416) but higher than that of Vázquez-Lima et al (9). In line with previous studies (12, 13), differences according to age were found with more suicide calls being made by people between the ages of 30 and 44 and between 45 and 59.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The average age of our sample (43.2 years) is similar to previous studies (1416) but higher than that of Vázquez-Lima et al (9). In line with previous studies (12, 13), differences according to age were found with more suicide calls being made by people between the ages of 30 and 44 and between 45 and 59.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, a higher proportion of calls mobilizing one health resource was found with its implicit economic cost. This result was similar to that of Jiménez-Hernández et al (13), who asserted that most suicidal behavior emergencies entailed a high economic cost because they mobilized one ambulance.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations